2021
DOI: 10.1037/edu0000631
|View full text |Cite
|
Sign up to set email alerts
|

A growth mindset lowers perceived cognitive load and improves learning: Integrating motivation to cognitive load.

Abstract: Many large-scale, school-based interventions have attempted to improve academic performance through promoting students' growth mindset, defined as the belief that one's intellectual ability can increase with practice and time. However, most have shown weak to no effects. Thus, it is important to examine how growth mindset might affect retention and transfer of learning, as well as process-related variables such as cognitive load. In a double-blind, randomized controlled experiment based on 138 secondary school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 81 publications
4
28
0
1
Order By: Relevance
“…This would also imply to follow students along a whole university year, and not just a few weeks. Nonetheless, recent research (Xu et al, 2021) clarify the beneficial role of GM induction on a defined, experimental learning performance similar to the present study,…”
Section: Limitations and Future Studiessupporting
confidence: 84%
“…This would also imply to follow students along a whole university year, and not just a few weeks. Nonetheless, recent research (Xu et al, 2021) clarify the beneficial role of GM induction on a defined, experimental learning performance similar to the present study,…”
Section: Limitations and Future Studiessupporting
confidence: 84%
“…Current research suggests that the interplay between motivation, cognitive load, and learning performance may be more complex than previously assumed. Xu et al (2020) conducted a study to assess whether learning performance, as well as the subjective feeling of cognitive load, can be modulated by learners' motivation, by using a growth mindset intervention (i.e., fostering learners' belief that they are capable of increasing their mental capacity through practice). The results of this study revealed that the inclusion of a motivation prompt, the growth mindset intervention, lowered levels of perceived cognitive load and fostered higher retention and transfer scores.…”
Section: Motivation In the Context Of Cognitive Load Theorymentioning
confidence: 99%
“…Musa, et al (2018) found similar results for arithmetic domain, and that not many students could perform transfer tests based on the general problem solving strategy. There are many instructions have been investigated by cognitive load theory in which assist students to construct and automate knowledge in efficient way (Xu, et al, 2021), as known that knowledge automation can help learners to transfer their learning (Paas & van Merriënboer, 2020). Without disregarding the instructions that had been used by the teachers, learners are also the factors influencing the transferability.…”
Section: Discussionmentioning
confidence: 99%